Hemobilia - Dogru, O; Cetinkaya, Z; Bulbuller, N; Camci, C; Aygen, E (Springer, 2003)
Background: Laparoscopic procedures are safe and effective treatment methods in experienced hands. However, complications have been reported for laparoscopic procedures. One of the complications of laparoscopic cholecystectomy is vascular injuries. Hepatic and cystic artery injuries may occur alone or in association with bile duct injury. Bleeding from arterial injury may be seen during operation or in the late postoperative period. One of the most significant pathologies leading to this rare phenomenon is hemobilia. Methods: We present a case of a 62-year-old woman who underwent routine laparoscopic cholecystectomy for cholelithiasis at another hospital. She presented 6 months later with the clinical feature of upper gastrointestinal bleeding. Results: There was a 42 x 40 x 11 mm anechoic lesion and an echoic pattern compatible with a metallic object was found in the subhepatic region using abdominal ultrasonography. In the endoscopic examination, fresh blood was found in the stomach. The source of hemorrhage could not be identified. Bulbus duodeni was normal but a fresh clot on the papilla of Vateri was seen on gastroduodenoscopic examination. Laparotomy was performed and the provisional diagnosis of hemobilia was reached. The injured hepatic artery and pseudoaneurysmatic structure were repaired. Conclusion: Hemobilia is a late complication of laparoscopic cholecystectomy. We believe that it is important to take into consideration that bile duct injuries may be accompanied by arterial pathology.
Keywords: laparoscopic cholecystectomy; hemobilia